Association of anxiety or depression with risk of recurrent cardiovascular events and death after myocardial infarction: A nationwide registry study. (15th June 2023) - Flygare, Oskar; Boberg, Julia; Rück, Christian; Hofmann, Robin; Leosdottir, Margret; Mataix-Cols, David; de la Cruz, Lorena Fernández; Richman, Peter; Wallert, John
Abstract: Background: Depression and anxiety are risk factors for patients with myocardial infarction (MI). However, the association of a previous psychiatric diagnosis of anxiety or depression, or only such self-reported symptoms, with cardiovascular outcomes and mortality post-MI has not been previously examined in the same nationwide cohort. Methods: We linked demographic, socioeconomic and clinical data from four nationwide Swedish registries for patients enrolled in cardiac rehabilitation (CR) after first-time MI (2006–2015, N = 45, 096). After multiple imputation, we applied Cox regression to estimate the post-MI outcome risk for patients with a previous psychiatric diagnosis of anxiety/depression (Diagnosis), patients with no formal diagnosis but self-reported symptoms of anxiety/depression (Symptoms), versus patients with neither Diagnosis nor Symptoms (Reference). Results: During one-year follow-up, fully adjusted models showed that patients with Diagnosis had a higher risk (hazard ratio [95%CI]) of all-cause mortality (1.86 [1.36, 2.53]), reinfarction (1.14 [1.06, 1.22]), their composite (1.15 [1.07, 1.23]), and an extended cardiovascular composite (1.19 [1.12, 1.26]), versus Reference, even though 77% reported no symptoms at the time of MI. In patients with Symptoms, estimates were also elevated yet somewhat attenuated compared to Reference. Findings were overall robust across multiple sensitivity analyses. Conclusions: Both a previous diagnosis, and present self-reported symptoms of anxiety or depression are associated with an increased risk of death and recurrent cardiovascular events in adults with first-time MI. Only screening for present symptoms is inadequate for assessing this excessive risk. Assessment of both psychiatric history and self-reported symptoms seems warranted for these patients. Graphical abstract: Unlabelled Image Highlights: Depression and anxiety are risk factors for patients with myocardial infarction (MI) Different operationalisations of depression and anxiety and their association with post MI risk have not been studied in the same nationwide cohort. We linked demographic, socioeconomic and clinical data from four nationwide Swedish registries for 45, 096 SWEDEHEART patients enrolled in cardiac rehabilitation (CR) after first-time MI. We estimated the post-MI risk of death and cardiovascular events for patients with (1) a previous psychiatric diagnosis of anxiety or depression, (2) no such diagnosis but instead present symptoms of anxiety or depression, vs (3) patients with neither diagnosis nor symptoms. Both a previous diagnosis, and symptoms of anxiety or depression were associated with an increased risk of death and recurrent cardiovascular events in adults with first-time MI. Only screening for present symptoms is inadequate for assessing this excessive risk in patients with first-time MI. Assessment of both psychiatric history and self-reported symptoms seems warranted for patients with first-time MI.